PENGARUH HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN JASA EKSPEDISI J&T EXPRESS (STUDI PADA MASYARAKAT KELURAHAN RAWABADAK UTARA, JAKARTA UTARA) - Nia Agustin; Rousdy Safari Tamba (JAMBIS : Jurnal Administrasi Bisnis, 2022)
This study aims to find out and analyze the effect of price and servicequality on decisions to use J&T Express Expedition services. Collecting data through a questionnaire with a Likert scale collection technique. The data used is primary data. The population in this studyis the population of community Rawa Badak Utara, which is 21,568 people. The sample obtained from the population is 100 respondents with a sampling technique is purposive sampling. This study uses a quantitative approach. Data calculation and analysis using SPSS version 28.0. The results showed that partially (t test) Price (X1) hada significant effect on the Decision to Use (Y) supported by the arithmetic value tcount > ttable (3.165 > 1.988) and the coefficient of determination of the r2 value obtained was 54.7%. Partially (t-test)Service Quality (X2) has a significant effect on Decision to Use (Y)supported by the calculated value of tcount > ttable (7.036 > 1.988) and the coefficient of determination of the value of r2 obtained is 66.9%. Simultaneously (f test) Price (X1) and Service Quality (X2) have a significant effect on the Decision to Use (Y) supported by fcount > ftable (113,031 > 3.09) and the coefficient of determinationof the value of r2 obtained is 70%..